Speciation of Cu, Se, Zn and Fe in blood serum of hemodialysed patients - Mestek, O; Komínková, J; Koplík, R; Zima, T; Miskusová, M; Stern, P (Sbornik lekarsky, 2002)
The speciation of trace elements in serum samples of hemodialysed patients was investigated using on-line connection of SEC and ICP-MS. The 0.02 mol/l TRIS-HCl buffer of pH 7.5 was used as mobile phase. The results of speciation as well as the total concentration data were compared with those of control group of healthy person. Alterations of total concentration were observed in case of selenium and zinc only. Iron was present in form of transferrin and ferritin, main amount of copper was bound to ceruloplasmin and selenium compounds were identified as selenoproteine P and glutathione peroxidase. The latter compound was detected in samples of control group only. The chromatograms of the other elements were similar and no substantial changes between both investigated groups were observed.
Keywords: selen; Selenium; Iron; zinek; mužské pohlaví; dialýza ledvin; Renal Dialysis; ženské pohlaví; měď; Zinc; železo; Humans; stopové prvky; Female; Trace Elements; Copper; lidé; Male